Gravity model of trade: unobserved heterogeneity and endogeneity - Chan, Felix; Greene, William; Harris, Mark N.; Konya, Laszlo (2014)
We consider the estimation of the Gravity model of trade, which involves ﬂows of trade, say exports, from country i to country j in time period t. We model the unobserved heterogeneities in export and import countries separately by proposing an easy-to-implement generalised method of moments estimator. The new estimator avoids the issues associated with the familiar ﬁxed eﬀects treatment of the unobserved heterogeneity in this type of model and at the same time is consistent and asymptotically normal in the presence of potentially endogenous covariates. The proposed approach can also estimate the unobserved heterogeneities and therefore allows further analysis on the individual, as well as time varying, characteristics of both import and export countries.